China in transition - Barton, Nicholas (Hong Kong : Educational Film Services, 1985)
Covers the history of China from the proclaimation of T'an Chien as emperor of the Sui dynasty to the periods of the T'ang and Sung dynasties
Copy available in DVD format
Based on the Times atlas of world history
Keywords: China -- History -- Sui dynasty, 581-618; China -- History -- T'ang dynasty, 618-907